In situ patterned micro 3D liver constructs for parallel toxicology testing in a fluidic device. (11th September 2015) - Skardal, Aleksander; Devarasetty, Mahesh; Soker, Shay; Hall, Adam R
Abstract: 3D tissue models are increasingly being implemented for drug and toxicology testing. However, the creation of tissue-engineered constructs for this purpose often relies on complex biofabrication techniques that are time consuming, expensive, and difficult to scale up. Here, we describe a strategy for realizing multiple tissue constructs in a parallel microfluidic platform using an approach that is simple and can be easily scaled for high-throughput formats. Liver cells mixed with a UV-crosslinkable hydrogel solution are introduced into parallel channels of a sealed microfluidic device and photopatterned to produce stable tissue constructs in situ . The remaining uncrosslinked material is washed away, leaving the structures in place. By using a hydrogel that specifically mimics the properties of the natural extracellular matrix, we closely emulate native tissue, resulting in constructs that remain stable and functional in the device during a 7-day culture time course under recirculating media flow. As proof of principle for toxicology analysis, we expose the constructs to ethyl alcohol (0–500 mM) and show that the cell viability and the secretion of urea and albumin decrease with increasing alcohol exposure, while markers for cell damage increase.